Reproductive ecology of a critically endangered alpine galaxiid. Issue 3 (28th January 2021) - Allan, Hugh; Duncan, Richard P.; Unmack, Peter; White, Duanne; Lintermans, Mark
Abstract: Stocky galaxias Galaxias tantangara is a newly described freshwater fish restricted to a single population, occupying a 3 km reach of a small headwater stream in the upper Murrumbidgee River catchment of south‐eastern Australia. This species is listed as critically endangered under IUCN Red List criteria, and knowledge of the species' ecology is critical for future conservation efforts to establish additional populations by translocation and captive breeding. This study details the first account of spawning and reproductive ecology of G. tantangara, including reproductive development, timing of spawning and a description of one spawning site. Peak gonadosomatic index was observed in March/April in males and in October in females. Absolute fecundity ranged from 211 oocytes for a 76 mm length to caudal fork (LCF) fish to 810 oocytes for a 100 mm LCF fish. The observation of spent females in mid‐November 2017 and discovery of an egg mass 8 days later suggest that spawning had occurred, and over a relatively short period. Larvae were subsequently detected in monthly electrofishing surveys in December 2017. Findings from this study provide new understanding of existing and future threats to G. tantangara and have important implications for conservation management of not only this species but also other closely related threatened Galaxias species.